The Enlarged European Union : Unity and Diversity. - Mair, Peter (Taylor and Francis, 2012)
Focusing upon the emerging patterns of unity and diversity in the enlarged European Union, this study explores enlargement from the East and the impact this will have on the future identity of Europe.